Recent advances in small molecule dye-based nanotheranostics for NIR-II photoacoustic imaging-guided cancer therapy - Zhou, Wen; Yin, Likun; Zhang, Xuheng; Liang, Tingting; Guo, Zixin; Liu, Yaxin; Xie, Chen; Fan, Quli (Frontiers in Bioengineering and Biotechnology, 2022)
Photoacoustic (PA) imaging in the second near-infrared (NIR-II) window has gained more and more attention in recent years and showed great potential in the field of bioimaging. Until now, numerous materials have been developed as contrast agents for NIR-II PA imaging. Among them, small molecule dyes hold unique advantages such as definite structures and capability of fast clearance from body. By virtue of these advantages, small molecule dyes-constructed nanoparticles have relatively small size and show promise in the clinical translation. Thus, in this minireview, we summarize recent advances in small molecule dyes-based nanotheranostics for NIR-II PA imaging and cancer therapy. Studies about NIR-II PA imaging-guided phototherapy are first introduced. Then, NIR-II PA imaging-guided phototherapy-based combination therapeutic systems are reviewed. Finally, the conclusion and perspectives of this field are summarized and discussed.